2015
DOI: 10.1073/pnas.1502474112
|View full text |Cite|
|
Sign up to set email alerts
|

LINE-1 expression and retrotransposition in Barrett’s esophagus and esophageal carcinoma

Abstract: Barrett's esophagus (BE) is a common disease in which the lining of the esophagus transitions from stratified squamous epithelium to metaplastic columnar epithelium that predisposes individuals to developing esophageal adenocarcinoma (EAC). We hypothesized that BE provides a unique environment for increased long-interspersed element 1 (LINE-1 or L1) retrotransposition. To this end, we evaluated 5 patients with benign BE, 5 patients with BE and concomitant EAC, and 10 additional patients with EAC to determine L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
125
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(139 citation statements)
references
References 60 publications
9
125
2
Order By: Relevance
“…We observed increased expression of LINE elements, consistent with recent reports describing increased LINE-1 retrotransposition activity in both BE and EAC (21). Interestingly, however, Alu elements, primate-specific short interspersed nuclear elements (SINE), showed almost uniform downregulation in EAC compared with premalignant Barrett's and normal squamous tissues.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed increased expression of LINE elements, consistent with recent reports describing increased LINE-1 retrotransposition activity in both BE and EAC (21). Interestingly, however, Alu elements, primate-specific short interspersed nuclear elements (SINE), showed almost uniform downregulation in EAC compared with premalignant Barrett's and normal squamous tissues.…”
Section: Discussionsupporting
confidence: 90%
“…For example, repeat elements, which make up two thirds of the human genome (18), have been associated with cancer (19) and double stranded breaks (20), and long-interspersed nuclear element 1 (LINE-1) retrotransposition is increased in EAC and Barrett's (21).…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is even more true for Alu insertion variants (45,46). These studies have also demonstrated that several types of epithelial cancers acquire somatic insertions of LINE-1 as they develop (15,19,24,26). Recent projects mining whole-genome sequencing data have extended our understanding of the scope of heritable LINE-1 insertions (20,21,47) and somatic retrotransposition (22,23,48) greatly.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, however, strategies for mapping these elements have been developed based on selective PCR amplification (15)(16)(17), hybridizationbased enrichment (18,19), and read selection from wholegenome sequencing data (20)(21)(22). These studies underscore the continued activity of LINE-1 in modern humans, and demonstrated somatic insertions in several types of human malignancy (15,19,(22)(23)(24)(25)(26)(27).…”
Section: Significancementioning
confidence: 99%
“…Until recently, L1 elements were thought to be mobilized primarily in the germline and then silenced in somatic cells throughout adulthood. However, several recent reports have shown that L1 elements are active in at least some adult somatic tissues, including the brain (Muotri et al 2005;Coufal et al 2009;Baillie et al 2011;Evrony et al 2012;Upton et al 2015) and epithelial somatic tumors Iskow et al 2010;Lee et al 2012;Solyom et al 2012;Shukla et al 2013;Helman et al 2014;Tubio et al 2014;Doucet-O'Hare et al 2015;Ewing et al 2015;Rodic et al 2015). These observations have led to the suggestion that L1 might play a role in initiating human cancers by mutating specific oncogenes or tumor suppressor genes in somatic cells.…”
mentioning
confidence: 99%